Human and social capital facing challenges of economic convergence processes in Poland - Małgorzata Wosiek (Managerial Economics)
The article deals with the study of the role of human and social capital in shaping the processes of regional development in Poland in 2002–2014. The study is aimed at seeking answers to the question whether and to what extent the characteristics of human and social capital developmentimpeded or fostered the achievement of convergence in living standards (GDP per capita) in regional systems (NUTS-2). The following tools were used: multidimensional statistical exploratory analysis – the cluster analysis (Ward’s, k-means), linear ordering – as well as correlation analysis and measures of statistical dispersion. The analysis confirm a stronger link of the processes of economic development in Polish regions with human capital than in those with social capital, whereby there is evidence indicating that it was rather a higher level of the economic development that stimulated changes in human capital and the reverse impact of human capital on the change in the GDP per capita was weaker. When it comes to the educational component of human capital, it can be assumed that this component of human capital could have had a more polarizing than converging impact. The social capital did not mitigate nor strengthen the polarizingimpact of human capital. There was, therefore, n confirmation to the hypothesis that intangible factors – human and social capitals – contributed to the convergence in living standards among regions in Poland in 2002–2014.